Cancer neuroscience in head and neck: interactions, modulation, and therapeutic strategies - Hanrui Wang; Xiaoyu Song; Hui Shen; Wanchen Liu; Yao Wang; Mingjun Zhang; Ting Yang; Yakui Mou; Chao Ren; Xicheng Song (Molecular Cancer)
Abstract Head and neck cancer (HNC) is an aggressive malignancy with significant effects on the innervation. Not only is it at the top of the cancer spectrum with a dismal prognosis, but it also imposes considerable stress on patients and society owing to frequent neurological symptoms. With progress in cancer neuroscience, the interactions between HNC and the nervous system, as well as the underlying mechanisms, have become increasingly clear. Compelling evidence suggests communication of information between cancer and nerve cells and devastation of the neurological system with tumor growth. However, the thorough grasp of HNC in cancer neuroscience has been severely constrained by the intricacy of HNC and fragmented research. This review comprehensively organizes and summarizes the latest research on the crosstalk between HNC and the nervous system. It aims to clarify various aspects of the neurological system in HNC, including the physiology, progression, and treatment of cancer. Furthermore, the opportunities and challenges of cancer neuroscience in HNC are discussed, which offers fresh perspectives on the neurological aspects of HNC diagnosis and management.